2022
DOI: 10.1007/s10067-022-06452-0
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ perceptions about antineutrophil cytoplasmic antibody-associated vasculitis: an online survey report in the time of the COVID-19 pandemic

Abstract: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAV) are characterized by necrotizing inflammation of small and medium-size vessels that often manifest with devastating multi-organ effects. They present with a myriad of systemic features and require potent immunosuppression. Since they are uncommonly encountered in clinical practice, it is necessary to understand physicians’ knowledge and perceptions about this group of diseases. An online questionnaire was designed featuring 28 questions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As shown by the results of an international survey that was developed to study the knowledge and perceptions of medical professionals about the diagnosis and treatment of ANCA-associated vasculitis, the perception of systemic vasculitis differs in different countries. This study also revealed the need to update knowledge and awareness of small vessel vasculitis among the entire medical community since its inception [ 26 ]. To increase the level of knowledge about systemic vasculitis, which doctors of outpatient services and hospitals of various profiles may encounter in practice, it is necessary to develop educational programs and resources for continuing professional education for doctors with an emphasis on rare autoimmune pathologies, and in particular systemic vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by the results of an international survey that was developed to study the knowledge and perceptions of medical professionals about the diagnosis and treatment of ANCA-associated vasculitis, the perception of systemic vasculitis differs in different countries. This study also revealed the need to update knowledge and awareness of small vessel vasculitis among the entire medical community since its inception [ 26 ]. To increase the level of knowledge about systemic vasculitis, which doctors of outpatient services and hospitals of various profiles may encounter in practice, it is necessary to develop educational programs and resources for continuing professional education for doctors with an emphasis on rare autoimmune pathologies, and in particular systemic vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, some forms of vasculitis were observed during or after COVID-19 infection and recovery, and several cases of vaccine-related anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) were reported following vaccination or a booster dose. 3 4 5 Recently, it has been reported that eosinophilic granulomatosis with polyangiitis (EGPA) was diagnosed after the second dose of COVID-19 vaccination, and early diagnosis on patients with EGPA had a recurrence of severe polyneuropathy after vaccination. 6 7 Here, we report the first case of de novo EGPA after COVID-19 vaccination in Korea.…”
Section: Introductionmentioning
confidence: 99%